Validitas Virtual Lab Biologi Berbasis Pendekatan Saintifik pada Materi Struktur dan Fungsi Jaringan Tumbuhan - Dessy Rahmadita Fitriani; Sri Amintarti; Maulana Khalid Riefani (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2022)
The pandemic that has occurred around the world has affected various areas of life, including education. Learning in schools has been directed at distance learning, including biology practicum activities in the laboratory. Teachers are required to innovate and create interactive media. One of the interactive learning media that can connect the subject and object of learning is a virtual lab. Learning media must be suitable for use in the learning process. This study aims to describe the feasibility of a virtual lab based on a scientific approach on the structure and function of plant tissue. Research and development carried out using the Borg & Gall (1983) model, until the main product revision stage. The feasibility of learning media resulted from expert validation and user readability tests. Expert validation shows that the virtual biology lab based on a scientific approach is a very valid category. The readability test in a virtual biology lab based on a scientific approach showed a very good category. The virtual lab learning media based on a scientific approach to the material on the structure and function of plant tissue can be used independently or guided in distance learning.